Strengthening the delivery of integrated physical health care for adults experiencing serious mental illness: a scoping review of interventions in mental health settings - Munazzah Ambreen; Sihan Zhang; Osnat C. Melamed; Osnat C. Melamed; Christopher Canning; Christopher Canning; Brian Lo; Brian Lo; Sri Mahavir Agarwal; Sri Mahavir Agarwal; Amer M. Burhan; Amer M. Burhan; et al. (Frontiers in Health Services)
Individuals living with serious mental illness (SMI) face significant barriers to accessing appropriate physical health care, poorer associated health outcomes and premature mortality compared to the general population. This scoping review examines service delivery models and clinical practices supporting the integration of physical health care for adults with SMI within mental health settings, and their outcomes. Searches of four academic databases yielded 65 academic articles. Most integrated service delivery models were implemented in community mental health settings in the United States and incorporated elements of Wagner's Chronic Care Model, emphasizing delivery-system redesign, patient self-management support and use of clinical information systems. In most outcome studies, integrated care models were associated with improvements in primary care access and preventative screening rates, while other physical health indicators and emergency and inpatient service use demonstrated promising but mixed results. Implementation challenges of integrated service delivery models included securing financial resources and maintaining effective use of clinical information systems, among others. Successful implementation was facilitated by effective teamwork, care coordination, and administrative and leadership support. Study findings highlight the complexity of integrating physical health care in mental health settings, and the longer timeframes needed to observe changes in some outcomes. The review further underscores the need for ongoing efforts to advance integrated care delivery in mental health settings and the importance of longitudinal data collection to fully assess and optimize the implementation and outcomes of these interventions.Systematic Review Registration:https://doi.org/10.17605/OSF.IO/3T9VK.